Transition from a maternal to external nitrogen source in maize seedlings. Issue 4 (April 2017) - Sabermanesh, Kasra; Holtham, Luke R.; George, Jessey; Roessner, Ute; Boughton, Berin A.; Heuer, Sigrid; Tester, Mark; Plett, Darren C.; Garnett, Trevor P.
Abstract: Maximizing NO3 − uptake during seedling development is important as it has a major influence on plant growth and yield. However, little is known about the processes leading to, and involved in, the initiation of root NO3 − uptake capacity in developing seedlings. This study examines the physiological processes involved in root NO3 − uptake and metabolism, to gain an understanding of how the NO3 − uptake system responds to meet demand as maize seedlings transition from seed N use to external N capture. The concentrations of seed‐derived free amino acids within root and shoot tissues are initially high, but decrease rapidly until stabilizing eight days after imbibition (DAI). Similarly, shoot N% decreases, but does not stabilize until 12–13 DAI. Following the decrease in free amino acid concentrations, root NO3 − uptake capacity increases until shoot N% stabilizes. The increase in root NO3 − uptake capacity corresponds with a rapid rise in transcript levels of putative NO3 − transporters, ZmNRT2.1 and ZmNRT2.2 . The processes underlying the increase in root NO3 − uptake capacity to meet N demand provide an insight into the processes controlling N uptake. Abstract : Root NO3 − uptake capacity is regulated to meet plant nitrogen demand. To develop a model detailing it, we exploited a seedling's transition from seed nitrogen use to external nitrogen capture.